Gestational trophoblastic disease associated with ectopic pregnancy: A report of three cases. - Hadzi-Nicheva, Biljana; Prodanova, Irina; Yashar, Genghis; Kubelka-Sabit, Katerina; Grncharovska, Zlata; Basheska, Neli (Springer, 2003)
Introduction: Gestational trophoblastic diseases (GTD) are extremely rare conditions, especially the ones associated with ectopic pregnancies (EP). Case reports: Only three cases (0.26%, 3/1133) of GTD associated with EP were diagnosed at the Department of Histopathology and Clinical Cytology in the last 14 years. The first patient, age 29 underwent salpingectomy for clinical suspicion of tubal pregnancy, whereas in the second, age 49 hysterectomy with bilateral salpingo-oophprectomy (HSOP) was performed for a clinical diagnosis of ovarian endometriosis. The third patient, age 42 underwent HSOP for malignant ovarian tumour which metastasised to lungs. Pathological findings: Chorionic villi were found in the tubal lumen of the first patient, showing marked hydropic degeneration, reduced/absent vascularisation and excessive trophoblastic cell growth. Diagnosis of partial hydatiform mole was established, and the patient remained under surveillance for the HCG level. Atypical trophoblastic cells, which penetrated the full thickness of the tubal wall and invaded the ovarian blood vessels of the second patient, led to the diagnosis of an invasive mole. The third patient was diagnosed with choriocarcinoma due to the presence of a tumour consisting of malignant trophoblastic cells that infiltrated the right ovary, tube and uterine cornu. The last two patients received chemotherapy and have been well for 15 and 118 months, respectively. Conclusion: Due to extremely low incidence of GTD associated with EP, these entities are rarely clinically recognised. Therefore, a careful histopathologic examination of the adnexal masses is essential for the establishment of the correct diagnosis and further treatment of the patients.
Keywords: gestational trophoblastic disease; ectopic pregnancy; hydatiform mole; invasive mole; gestational choriocarcinoma